2021
DOI: 10.52586/5062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sterilization procedures on the physical and mechanical properties of rotating endodontic instruments: a systematic review and network meta-analysis

Abstract: Introduction 3. Materials and methods 4. Results 5. Discussion 5.1 Cyclic fatigue 5.2 Deformations and torsional fatigue 5.3 Corrosion, topographic and surface alterations 5.4 Cutting efficiency 6. Conclusions 7. Author contributions 8. Ethics approval and consent to participate 9. Acknowledgment 10. Funding 11. Conflict of interest 12. References Abbreviations: PRISMA, Preferred Reporting Items for Systematic reviews and Meta-Analyses; SEM, scanning electron microscopy; AFM, atomic force microscopy; AMR, arit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 98 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…In conclusion, there is a potential shape recovery effect and increased cyclic fatigue resistance after autoclaving. However, not all studies agree ( Dioguardi et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, there is a potential shape recovery effect and increased cyclic fatigue resistance after autoclaving. However, not all studies agree ( Dioguardi et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%
“…To maximize the benefit of the improved lifespans by reusing these instruments multiple times, autoclave sterilization procedures are essential. However, these procedures may also affect the instruments’ physical and mechanical properties ( Dioguardi et al, 2021 ). Therefore, this study evaluated the effect of multiple autoclave cycles on the cyclic fatigue resistance of three newly developed heat-treated NiTi files (ETP, PTG, and TN).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the effects of autoclave sterilization on the cyclic fatigue resistance of heat-treated instruments revealed high investigation method heterogeneity and a general lack of standardization, in turn impairing meaningful comparisons between different studies and/or the formulation of evidence-based conclusions ( Silva et al, 2020 ). Another systematic review similarly reported conflicting findings; however, the authors concluded that NiTi files exhibit a trend toward improved cyclic fatigue resistance following autoclave sterilization ( Dioguardi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies indicate the influence of autoclave sterilization on the cyclic fatigue and strength of NiTi instruments, but the results are controversial [24]. The results published in existing studies seem incomplete and the results differ for different types of instruments [25].…”
Section: Discussionmentioning
confidence: 99%